2015
DOI: 10.1093/cvr/cvv137
|View full text |Cite
|
Sign up to set email alerts
|

Circulating mitochondrial DNA and Toll-like receptor 9 are associated with vascular dysfunction in spontaneously hypertensive rats

Abstract: Circulating mtDNA and impaired deoxyribonuclease activity may lead to the activation of the innate immune system, via TLR9, and contribute to elevated arterial pressure and vascular dysfunction in SHR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
154
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(157 citation statements)
references
References 59 publications
2
154
1
Order By: Relevance
“…2 Previously, we observed that TLR9 was able to increase arterial blood pressure and cause endothelial dysfunction in rats with a normotensive background. 8 Nonetheless, the link between the innate immune system and the subsequent recruitment of the adaptive immune system in hypertensive rats remains unclear. Therefore, in this investigation, we hypothesized that inhibition of TLR9 with the lysosomotropic agent chloroquine (CQ), which has long been used as an inhibitor of endosomal TLR signaling, [11][12][13] would lower blood pressure and prevent the subsequent recruitment of immune cells to the vasculature in SHR.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Previously, we observed that TLR9 was able to increase arterial blood pressure and cause endothelial dysfunction in rats with a normotensive background. 8 Nonetheless, the link between the innate immune system and the subsequent recruitment of the adaptive immune system in hypertensive rats remains unclear. Therefore, in this investigation, we hypothesized that inhibition of TLR9 with the lysosomotropic agent chloroquine (CQ), which has long been used as an inhibitor of endosomal TLR signaling, [11][12][13] would lower blood pressure and prevent the subsequent recruitment of immune cells to the vasculature in SHR.…”
Section: Methodsmentioning
confidence: 99%
“…2,7 We have recently observed that mitochondrial DNA (mtDNA), a DAMP that activates TLR9, is increased in the circulation of spontaneously hypertensive rats (SHR). 8 Specifically, TLR9 recognizes unmethylated cytosine-phosphate-guanine (CpG) dinucleotides and these are common in prokaryotic DNA and mtDNA, but not nuclear DNA. 9 Upon recognition of unmethylated CpG dinucleotides in …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Because dysfunction and abnormal signaling in the main structural elements of the vasculature, such as endothelial cells and smooth muscle cells, are characteristic hypertension-associated vascular complications, [4][5][6][7][8][9] and functional impairments in these cells are observed in hypertensive patients and animal models of the disease, [10][11][12][13][14][15][16][17][18][19] a comprehensive understanding of the underlying mechanisms is indispensable for preventing and treating such complications.…”
mentioning
confidence: 99%
“…7 In their study published in the current issue of American Journal of Hypertension, 8 these investigators extend their findings by testing a mechanism of intracellular TLR activation, particularly TLR9, in SHR hypertension. Chloroquine, a drug known as an effective antimalarial therapeutic agent, blocks endosomal maturation 9 by inhibiting vesicular acidification that is also required for TLR9 signaling.…”
mentioning
confidence: 92%